1996
DOI: 10.1080/02652039609374457
|View full text |Cite
|
Sign up to set email alerts
|

Migration from plasticized poly(vinyl chloride) into fatty media: Importance of simulant selectivity for the choice of volatile fatty simulants

Abstract: An investigation was carried out to determine whether isooctane and ethanol behave like sunflower oil as fatty simulants for overall and for specific migration from PVC containing aromatic plasticizers (bis-2-ethylhexyl phthalate and tris-2-ethylhexyl trimellitate). In these films, the partition coefficients of migrants between simulant and polymer play a major role. The affinities of isooctane and of sunflower oil to all migrants were similar and isooctane can be considered as an alternative fatty simulant fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Some authors (Dopico-García et al, 2006;Feigenbaum, Bouquant, Hamdami et al, 1997;Hamdani & Feigenbaum, 1996;Rojas de Gante, 2002) have studied the thermal effect on specific migration under different temperature conditions, although little work has been reported on the suitability of alternative food simulants for migration testing at high temperatures (Galotto & Guarda, 2004). Widen, Leufven, and Nielsen(2004) showed that after 3 month storage, the migration of benzaldehyde form PET bottles into acetic acid increased by about the three times when the storage temperature increased from 20 to 40°C.…”
Section: Introductionmentioning
confidence: 98%
“…Some authors (Dopico-García et al, 2006;Feigenbaum, Bouquant, Hamdami et al, 1997;Hamdani & Feigenbaum, 1996;Rojas de Gante, 2002) have studied the thermal effect on specific migration under different temperature conditions, although little work has been reported on the suitability of alternative food simulants for migration testing at high temperatures (Galotto & Guarda, 2004). Widen, Leufven, and Nielsen(2004) showed that after 3 month storage, the migration of benzaldehyde form PET bottles into acetic acid increased by about the three times when the storage temperature increased from 20 to 40°C.…”
Section: Introductionmentioning
confidence: 98%
“…To prevent the plasticizer migrating from the inner PVC matrix to the surface of the product or the space has great value. 8,9 In this article, the synthesis and properties of PMMA-clay hybrid and its migration resistance to the plasticizer in PVC/PMMA-clay composite were studied. Results show that, when a specific ammonium ion is chosen as the intercalating reagent, MMT dispersed homogeneously in methyl methacrylate (MMA) monomer that allows MMT dispersing in PMMA matrix in the monolayer form.…”
Section: Introductionmentioning
confidence: 99%
“…There are several methods reported in the literature for the determination of migrating plasticizers, such as GC (both direct and indirect), GC/MS, pyrolysis-GC/MS, HPLC, FTIR, 1 H NMR and radioanalytical techniques (Castle, Jickells, Sharman, Gramshaw, & Gilbert, 1988;Cooper et al, 1998;Goulas & Kontominas, 1996;Hamdani & Feigenbaum, 1996;Hammarling et al, 1998;Nerin et al, 1992;Till et al, 1982;Tsumura et al, 2002;Wang, 2000).…”
Section: Introductionmentioning
confidence: 99%